Voice synthesizer system using microcontroller - Ismail, Noor Kamila (2008)
This study is carried out to design and implement a system that can produce synthetic voice using microcontroller PIC 16F877. It is also done to investigate the quality of the voice produce by the UM5100 voice processor chip. This project is also carried out to test and determine how to generate words such as "hello", "good" and "thank you" using this system. The research methodology proposed for this project starts with the hardware development, writing a program to produce data needed to experiment with the voice processor chip and then loading the program and storing it into the PIC. Later, a system testing is done for data collection and lastly documenting the results into technical papers, thesis and presentation slides.